Butterfly effect in porous Bénard convection heated from below - Siri Z.; Liew K.Y.; Ibrahim R.I. (American Institute of Physics Inc., 2024)
Transition from steady to chaos for the onset of Bénard convection in porous medium was analyzed. The governing equation is reduced to ordinary differential equation and solved using built in MATLAB ODE45. The transition from steady to chaos take over from a limit cycle followed by homoclinic explosion.